2020
DOI: 10.30802/aalas-jaalas-19-000067
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Efficacy of Tricaine Methanesulfonate (MS222) Solution After Long-Term Storage

Abstract: Tricaine methanesulfonate (MS222) is widely used for the anesthesia and euthanasia of laboratory zebrafish. Fresh solutions have been recommended for each use; however, researchers often mix and store concentrated stock solutions for convenience and to reduce occupational exposure and environmental waste. While this is common practice, published guidelines are often inconsistent. Thus, the objective of this study was to evaluate the stability and anesthetic efficacy of MS222 after long-term storage and to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…To test whether manipulations of other neuromodulators can affect the branching dynamics of the PVD, we utilized two anesthetics: tetramisole, which activates the nematode nicotinic acetylcholine receptors inducing muscle contraction (Aceves, Erlij et al, 1970) and tricaine, which modulates neuronal activity by blocking sodium channels (Katz, Chu et al, 2020) and analyzed their effects during 2-3 h of time lapse movies of crowded and isolated animals. We first tested the commonly used mixture of 0.1% tricaine and 0.01% tetramisole (the racemic mixture of the enantiomer levamisole) (Kravtsov et al, 2017) and found that it induces more growth than retraction of ectopic branches in crowded animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether manipulations of other neuromodulators can affect the branching dynamics of the PVD, we utilized two anesthetics: tetramisole, which activates the nematode nicotinic acetylcholine receptors inducing muscle contraction (Aceves, Erlij et al, 1970) and tricaine, which modulates neuronal activity by blocking sodium channels (Katz, Chu et al, 2020) and analyzed their effects during 2-3 h of time lapse movies of crowded and isolated animals. We first tested the commonly used mixture of 0.1% tricaine and 0.01% tetramisole (the racemic mixture of the enantiomer levamisole) (Kravtsov et al, 2017) and found that it induces more growth than retraction of ectopic branches in crowded animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The groups of zebrafish mentioned above were placed in 6-well plates with 6 fish per hole, and then the data of swimming behavior of zebrafish were recorded and analyzed by animal behavior analyzer. After 10 DPF, zebrafish were anesthetized with MS-222 solution, fixed with 4% paraformaldehyde solution, and dyed with Alizarin Red S. The final step of pretreatment was bleaching and decolorizing [ 37 ]. Lastly, the bone staining of zebrafish was observed under the microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The adopted approach to parasite quantification was built upon established methods from prior monogenean studies [46]. To facilitate the examination, Korean rockfish with M. sebastis infections were anesthetized using MS222 solution at a dose of 100 mg/L [47]. Subsequently, individual gills were meticulously inspected with forceps and tweezers, and we conducted a precise enumeration of the adult M. sebastis parasites present in each culture tank.…”
Section: In Vivo Assessment Of M Sebastis Efficacy To Salinomycinmentioning
confidence: 99%